An Unusual Endoscopic Image of a Submucosal Angiodysplasia - Rita Carvalho; Nuno Almeida; Manuela Ferreira; Pedro Amaro; António Bernardes; Maria Augusta Cipriano; J. M. Romãozinho; Hermano Gouveia; Carlos Sofia (Case Reports in Gastrointestinal Medicine)
Obscure gastrointestinal bleeding is responsible for 2–10% of the cases of digestive bleeding. Angiodysplasia is the most common cause. The authors report a case of a 70-year-old female patient admitted to our Gastrointestinal Intensive Care Unit with a significant digestive bleeding. Standard upper and lower endoscopy showed no abnormalities, and we decided to perform a capsule enteroscopy that revealed a submucosal nodule with active bleeding in the jejunum. An intraoperative enteroscopy confirmed the presence of a small submucosal lesion with a central ulceration, and subsequently a segmental enterectomy was performed. Surprisingly, the histopathological diagnosis was angiodysplasia. The patient remains well after a two-year period of follow-up. We present this case of obscure/overt gastrointestinal bleeding to emphasize the role of capsule and intraoperative enteroscopy in the evaluation of these situations, and because of the unusual endoscopic appearance of the angiodysplasia responsible for the hemorrhage.